Intestinal parasitic infections amongst Orang Asli (indigenous) in Malaysia: has socioeconomic development alleviated the problem? - Lim, Y.A.L.; Romano, N.; Colin, N.; Chow, S.C.; Smith, H.V. (2009)
Orang Asli are the indigenous minority peoples of peninsular Malaysia. Despite proactive socioeconomic development initiated by the Malaysian Government in upgrading the quality of life of the Orang Asli communities since 1978, they still remained poor with a current poverty rate of 76.9. Poverty exacerbates the health problems faced by these communities which include malnourishment, high incidences of infectious diseases (eg. tuberculosis, leprosy, malaria) and the perpetual problem with intestinal parasitic infections. Studies reported that the mean infection rate of intestinal parasitic infections in Orang Asli communities has reduced from 91.1 in 1978, to 64.1 in the subsequent years. Although the results was encouraging, it has to be interpreted with caution because nearly 80 of studies carried out after 1978 still reported high prevalence (i.e. >50) of soil-transmitted helminthiases (STH) among Orang Asli communities. Prior to 1978, hookworm infection is the most predominant STH but today, trichuriasis is the most common STH infections. The risk factors for intestinal parasitic infections remained unchanged and studies conducted in recent years suggested that severe STH infections contributed to malnutrition, iron deficiency anaemia and low serum retinol in Orang Asli communities. In addition, STH may also contribute to poor cognitive functions and learning ability Improvements in socioeconomic status in Malaysia have shown positive impact on the reduction of intestinal parasitic infections in other communities however, this positive impact is less significant in the Orang Asli communities. In view of this, a national parasitic infections baseline data on morbidity and mortality in the 18 subgroups of Orang Asli, will assist in identifying intervention programmes required by these communities. It is hope that the adoption of strategies highlighted in the World Health Organisation-Healthy Village Initiatives (WHO-HVI) into Orang Asli communities will ensure the whole mechanism of delivery and empowerment by the government agencies become more efficient and productive in alleviating intestinal parasitic infections in these communities.